The impact of obstacles to health and rehabilitation services on functioning and disability: a prospective survey on the 12-months after discharge from specialist rehabilitation for acquired brain injury. Issue 20 (25th September 2022) - Legg, Melissa; Foster, Michele; Jones, Rachel; Kendall, Melissa; Fleming, Jennifer; Nielsen, Mandy; Kendall, Elizabeth; Borg, David; Geraghty, Timothy
Abstract: Purpose: Little is known about obstacles to health and rehabilitation services experienced by people with acquired brain injury (ABI) over time and what impact these have on recovery. This study utilised the International Classification of Functioning, Disability, and Health model to better understand the impact of service obstacles. The aims were: (1) describe and compare service obstacles reported in the 12-months post-discharge from inpatient rehabilitation; (2) examine service obstacles as a moderator of the relationship between functional impairment and activities and participation. Materials and methods: Prospective survey of 41 people who received ABI inpatient rehabilitation in Queensland, Australia. Validated self-report measures of service obstacles, functional impairment, and activities and participation were administered at 6- and 12-months post-discharge. Results: Transportation was the highest-rated obstacle at 6-months post-discharge, and this decreased at 12-months. Dissatisfaction with treatment resources and financial obstacles were, on average, low-to-moderate and remained constant. Specifically, the moderation analyses showed that financial obstacles may exacerbate the negative impact of functional impairment on independent living skills. Conclusions: Our findings suggest that people living in Queensland, Australia, who experience financial obstacles to services after brain injury may be at risk of poorer recovery outcomes. Rehabilitation policy should consider prioritising individuals who experience financial obstacles to accessing services. IMPLICATIONS FOR REHABILITATION: In Queensland, Australia, financial obstacles to accessing health services after brain injury may exacerbate the negative impact of functional impairment on independent living skills, in the first 12-months after hospital discharge. There may be a need to prioritize rehabilitation policy that targets individuals who experience financial obstacles to accessing health and rehabilitation services, after brain injury, irrespective of a health system's potential to enable access.